Built-in anti-leakage alloy pipe and production method thereof

By introducing crosslinking modifiers and montmorillonite into PE/PET alloy materials, a dynamic crosslinking network is formed, the creep deformation and leakage problems of PE pipes are solved, the creep resistance and leakage resistance of alloy pipes are improved, and the service life is extended.

CN120572799APending Publication Date: 2025-09-02ANHUI JIELANTE NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510722212.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-30
Publication Date
2025-09-02

AI Technical Summary

Technical Problem

PE pipes are prone to creep deformation and leakage under long-term hydrostatic loads. The interface bonding strength between PET and PE blend materials is low, resulting in high leakage risk, short service life, and poor weather resistance.

Method used

Using PE/PET alloy material as a built-in layer, the cross-linking modifier epoxidized polyamide dendrimer and montmorillonite are added to improve interface compatibility through the layered structure of the ester dynamic cross-linking network and montmorillonite, forming a dynamic cross-linking network to enhance the density of the material and anti-leakage properties.

Benefits of technology

It significantly improves the creep resistance, hydrostatic strength and leakage resistance of alloy pipes, extends service life, reduces the permeability rate and diffusion path of permeable molecules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005429721760000111
    Figure BDA0005429721760000111
  • Figure BDA0005429721760000112
    Figure BDA0005429721760000112
Patent Text Reader

Abstract

The invention discloses a built-in anti-leakage alloy pipe and a production method thereof, and belongs to the technical field of alloy pipes, the alloy pipe comprises a built-in layer and an outer layer; the built-in layer comprises the following raw materials in parts by mass: 10-20 parts of PET, 80-90 parts of carboxylated polyethylene, 5-10 parts of a cross-linking modifier, 2-5 parts of an antioxidant and 3-6 parts of montmorillonite, and the cross-linking modifier is an epoxidized polyamidoamine dendrimer. The crosslinking modifier can help the built-in layer to form a dynamic three-dimensional crosslinking network in the processing process, the compactness of the internal structure of the alloy material is remarkably improved by utilizing the highly branched dendritic structure of the epoxidized polyamidoamine dendrimer, the non-deformability of the material under long-term load or high pressure is improved, the permeation rate of water molecules is reduced, and the service life of the material is prolonged. And moreover, the compatibility of two phases of the alloy material can be enhanced, interface defects are reduced, and a permeation path is blocked, so that the alloy pipe with excellent anti-permeation performance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloy pipes, and in particular relates to a built-in anti-leakage alloy pipe and a production method thereof. Background Art

[0002] PE (polyethylene) pipes are widely used in various fields such as municipal water supply and drainage, gas transportation, etc. because of their material characteristics such as high strength, high temperature resistance, corrosion resistance, non-toxicity and wear resistance.

[0003] However, PE pipes are prone to creep deformation under long-term hydrostatic loads. Using low-grade raw materials or doping with secondary materials can lead to cracks in the pipe wall under hoop stress, which can gradually expand into leakage channels. Furthermore, the PE molecular chains in PE pipes are sensitive to ultraviolet light and are prone to photooxidation with long-term exposure, causing microcracks on the pipe surface and still posing a risk of leakage.

[0004] PET (polyethylene terephthalate) has good wear resistance, heat resistance, chemical corrosion resistance and high mechanical strength. The alloy material obtained by blending it with PE can significantly improve the rigidity and heat resistance of PE and improve its chemical stability. Applying its alloy material to pipes can further improve the quality of the pipes.

[0005] However, the polarity difference between PET and PE results in a weak interface strength between the two phases. This leads to the formation of stress-concentrating micropores under hydrostatic loads, which can cause pipe leakage. Furthermore, the crystallization rates of PET and PE are mismatched, resulting in poor structural stability and difficulty adapting to extreme environmental changes. Leakage in these pipes during use not only wastes resources, pollutes the environment, and contaminates drinking water sources, but also shortens their service life and increases maintenance costs.

[0006] Therefore, there is an urgent need to obtain a pipe material with excellent performance, good weather resistance, long service life and anti-leakage performance. Summary of the Invention

[0007] The object of the present invention is to provide a built-in anti-leakage alloy pipe and a production method thereof, so as to solve the problem of poor anti-leakage performance of the alloy pipe.

[0008] The purpose of the present invention can be achieved through the following technical solutions:

[0009] In a first aspect, the present invention provides a built-in anti-leakage alloy pipe, the alloy pipe comprising an inner layer and an outer layer; the inner layer comprises the following raw materials in parts by weight:

[0010] PET 10-20 parts;

[0011] 80-90 parts of carboxylated polyethylene;

[0012] 5-10 parts of cross-linking modifier;

[0013] 2-5 parts of antioxidant;

[0014] 3-6 parts of montmorillonite;

[0015] The cross-linking modifier is an epoxidized polyamidoamine dendrimer.

[0016] Preferably, the antioxidant includes one or more combinations of antioxidant 1010, antioxidant 1076, antioxidant B225, antioxidant 168, antioxidant 626, and antioxidant DLTP.

[0017] By adopting the above technical solution, PE single pipe has certain limitations in mechanical properties, temperature resistance and corrosion resistance. The present invention adopts PE / PET alloy material as the inner layer of the pipe, and utilizes the advantages of good rigidity and wear resistance of PET material to improve the compressive strength and impact resistance of the pipe. After alloying, the chemical corrosion resistance of the material can be improved, thereby broadening the application range of the pipe.

[0018] At the same time, the present invention also adds a cross-linking modifier. Specifically, the cross-linking modifier is an epoxidized polyamide amine dendrimer. The present invention uses polyethylene that has been carboxylated to introduce carboxyl groups into the polyethylene molecular chain. During the processing, the epoxy groups in the cross-linking modifier can react with the carboxyl groups on the carboxylated polyethylene and the PET molecular chains respectively to form ester dynamic exchange bonds, thereby obtaining an alloy pipe with a dynamic cross-linking network.

[0019] On the one hand, polyamidoamine dendrimers have a highly branched tree-like structure. After forming a cross-linked network, they significantly enhance the density of the material's internal structure, thereby improving the material's creep resistance. They are also less susceptible to plastic deformation under high pressure and can maintain structural integrity when subjected to long-term hoop stress, significantly improving the hydrostatic strength of the internal layer of the PE / PET alloy material. The introduction of polyamidoamine dendrimers also reduces internal defects and molecular chain mobility through the dual effects of physical filling and chemical cross-linking, thereby improving the material's weather resistance and reducing the permeation rate of water molecules, thereby enhancing the material's anti-permeability properties.

[0020] On the other hand, the cross-linking modifier primarily forms ester dynamic exchange bonds with the PE / PET alloy, which offer greater stability and self-healing capabilities, creating a denser structure within the alloy. However, due to the poor compatibility of PET and PE blends, the alloy's interfacial bonding is poor. The introduction of dynamic exchange bonds can form an interpenetrating network across the PE / PET interface, enhancing compatibility between PET and PE, reducing interfacial defects, and inhibiting leakage paths. When the internal layer is subjected to internal pressure, the dynamic exchange bonds can effectively release stress, preventing crack propagation and thus improving the resulting alloy tubing's leak-proof properties.

[0021] The alloy material obtained by blending PE and PET has the problem of poor compatibility. Due to the inconsistent crystallization rates and shrinkage rates of the two, the processing performance is poor, and the built-in layer formed is prone to uneven thickness and surface warping.

[0022] In order to further improve the performance of the built-in layer material, montmorillonite is additionally added. The unique layered silicate structure of montmorillonite can provide a large number of heterogeneous nucleation sites for PE / PET alloy materials, which can reduce the crystallization activation energy and promote the formation of crystal nuclei. By optimizing the crystallinity of the material and reducing the grain boundary defects caused by crystallization differences, the processability of the material is improved, and a built-in layer raw material with stable performance is obtained.

[0023] At the same time, the addition of montmorillonite can strengthen the interface bonding of the alloy material through mechanical interlocking. The layered structure also extends the diffusion path of the penetrating molecules to a certain extent, reduces the diffusion rate of the penetrating molecules, and improves the barrier properties of gases and liquids, thereby enhancing the anti-leakage ability of the built-in layer.

[0024] Preferably, the raw materials of the carboxylated polyethylene include polyethylene, maleic anhydride and initiator in a mass ratio of 100:(1.5-2):(0.2-0.3).

[0025] Preferably, the initiator comprises one or a combination of dicumyl peroxide and dibenzoyl peroxide.

[0026] Preferably, the carboxylated polyethylene is prepared according to the following method:

[0027] Maleic anhydride and an initiator are added to a solvent, stirred and dissolved to obtain a mixed solution with a mass fraction of 5 to 10%; the mixed solution is evenly mixed with polyethylene, and then melt-extruded to obtain carboxylated polyethylene.

[0028] Preferably, the solvent comprises a combination of one or more of acetone, chloroform, ether and petroleum ether.

[0029] By adopting the above technical solution, the polyethylene used in the present invention is subjected to a carboxylation modification treatment. By modifying the polyolefin with anhydride, carboxyl groups are attached to the polyethylene molecular chain. This results in the carboxylated polyethylene and PET having relatively similar polarity characteristics, greatly reducing the polarity mismatch between the two, thereby reducing the interfacial tension between the two and promoting the mutual diffusion and entanglement between the polyethylene and PET segments. Simultaneously, the introduction of carboxyl groups can react with the epoxy groups in the cross-linking modifier to form a dynamic cross-linking network, further optimizing interfacial compatibility, and simultaneously improving the hydrostatic load resistance and weather resistance of the alloy material, thereby enhancing the anti-leakage performance of the resulting alloy pipe.

[0030] The three-dimensional interpenetrating network formed by dynamic cross-linking can significantly reduce the free volume and micropore defects between molecular chains. It utilizes the chemical bonding effect of the carboxyl groups of carboxylated polyethylene to eliminate microcracks at the interface of the alloy material, thereby blocking the permeation channels of liquid or gas along the phase interface and improving the anti-leakage and mechanical properties of the built-in layer.

[0031] Preferably, the raw materials of the epoxidized polyamidoamine dendrimer include polyamidoamine dendrimer and epichlorohydrin in a mass ratio of 1:(26-30).

[0032] Preferably, the epoxidized polyamidoamine dendrimer is prepared according to the following method:

[0033] Add polyamidoamine dendrimers to an alcohol solution, stir and mix, then add epichlorohydrin, raise the temperature to 50-60°C, stir and react for 5-6 hours, then add an alkaline catalyst, adjust the solution temperature to 30-35°C, continue stirring and react for 2-3 hours, and finally filter, extract, vacuum distill and dry to obtain epoxidized polyamidoamine dendrimers.

[0034] More preferably, the alcohol solution includes a combination of one or more of ethanol, methanol, isopropanol and ethylene glycol.

[0035] More preferably, the alkaline catalyst comprises a combination of one or more of an aqueous sodium hydroxide solution and an aqueous potassium hydroxide solution.

[0036] By adopting the above technical solution, the epoxy group and monochlorine substitution in epichlorohydrin are a type of strong electron-withdrawing group. The epoxy groups contained therein are easy to undergo ring-opening reactions. A ring-opening addition reaction occurs between the terminal amino group of the polyamide amine dendrimer and the epoxy group, and then an elimination reaction occurs under the action of an alkaline catalyst, and finally the epoxy group is introduced into the polyamide amine dendrimer.

[0037] The obtained epoxidized polyamide amine dendrimer can act as a cross-linking modifier to react with the carboxyl groups contained in the carboxylated polyethylene and PET molecular chains to form ester dynamic exchange bonds and a three-dimensional dynamic cross-linked network structure. This can not only optimize the interface compatibility without the need to add additional compatibility to improve the interface force, but also improve the density and stability of the built-in layer structure, improve the mechanical properties and hydrostatic strength of the alloy material, enable the alloy pipe to adapt to and withstand long-term or high-pressure loads, and improve the weather resistance of the total material, extend the service life of the alloy pipe, and improve the anti-leakage ability of the obtained alloy pipe.

[0038] Preferably, the montmorillonite is subjected to an organic treatment; the organic treatment comprises the following steps:

[0039] The montmorillonite is dispersed in water, stirred and dispersed at 60-65°C for 2-3 hours, then a cationic surfactant is added, the temperature is raised to 75-80°C, and the stirring reaction is continued for 2-3 hours. Finally, the organically treated montmorillonite is obtained by vacuum filtration, washing, drying, grinding and sieving.

[0040] Preferably, the mass ratio of montmorillonite to cationic surfactant is 1:(0.7-0.8); the cationic surfactant includes a combination of one or more of cetyltrimethylammonium bromide, octadecyltrimethylammonium chloride and octadecyldimethylbenzylammonium chloride.

[0041] By adopting the above technical solution, since montmorillonite is a hydrophilic layered silicate, when compounded with PE / PET polymer, the montmorillonite layer may agglomerate due to the difference in interfacial tension, thereby affecting the performance of the alloy material. Therefore, in the present invention, the montmorillonite can also be first subjected to an organic treatment, specifically:

[0042] Montmorillonite is intercalated and modified by cationic surfactants. On the one hand, the cationic surfactants enter the montmorillonite interlayers through ion exchange, replacing the original metal ions to increase the interlayer spacing, and the introduced hydrophobic alkyl chain segments can improve the dispersibility in the alloy material. The polar end groups can participate in the dynamic cross-linking network of the alloy material through hydrogen bonding to form a bridging structure, reducing agglomeration while improving the reinforcement effect of the alloy material.

[0043] On the other hand, organically modified montmorillonite can promote the formation of finer and more uniform spherulites in PET, thereby improving the heat resistance of the alloy material and its ability to adapt to environmental changes. Expanding the spacing between montmorillonite layers can also help form a more tortuous penetration path inside the alloy material, further increasing the barrier effect, thereby helping to improve the anti-leakage ability of the built-in layer.

[0044] Preferably, the material of the outer layer includes heat-resistant polyethylene.

[0045] By adopting the above technical solution, the present invention uses heat-resistant polyethylene as the main raw material for the outer layer of the alloy pipe. Compared with ordinary polyethylene, heat-resistant polyethylene can better withstand application fields such as heating and chemical pipelines, reduce interlayer stress cracking caused by hot and cold cycles, and improve the application range and service life of the alloy pipe.

[0046] Heat-resistant polyethylene also has high compressive strength and wear resistance, which can provide a high-density surface for the alloy pipe, blocking the penetration of external media. It also has good resistance to UV aging, reducing microcracks caused by oxidative degradation, and helping to improve the overall anti-leakage performance of the alloy pipe.

[0047] In a second aspect, the present invention provides a method for producing a built-in anti-leakage alloy pipe, comprising the following process steps:

[0048] S1. Weigh the corresponding parts by mass of the built-in layer raw materials, mix them evenly and then extrude and granulate them to obtain a built-in layer masterbatch;

[0049] S2. The inner layer masterbatch and the heat-resistant polyethylene are extruded through a two-layer co-extruder, wherein the inner layer masterbatch is extruded to form an inner layer, thereby obtaining an inner leakage-proof alloy pipe.

[0050] Preferably, the thickness ratio of the inner layer to the outer layer is (2-4):1.

[0051] Preferably, the temperature of the extrusion granulation in step S1 is 200-240°C.

[0052] Beneficial effects of the present invention:

[0053] 1. The alloy tube of the present invention is divided into an inner layer and an outer layer, wherein the raw material of the inner layer adopts PE / PET alloy material, PE is carboxylated polyethylene, and a dynamic three-dimensional cross-linked network can be formed between the alloy material and the cross-linking modifier, namely the epoxidized polyamide amine dendrimer during the processing. On the one hand, the highly branched tree structure of the epoxidized polyamide amine dendrimer can be utilized to significantly improve the density of the internal structure of the alloy material, improve the material's deformation resistance under long-term load or high pressure, and reduce the permeation rate of water molecules; on the other hand, the compatibility of the two phases of the alloy material can be enhanced, interface defects can be reduced, and permeation paths can be blocked, thereby obtaining an alloy tube with excellent anti-permeation performance.

[0054] 2. Montmorillonite is also added to the inner layer of the alloy pipe of the present invention. Montmorillonite can act as a nucleating agent, optimize the crystallization process of the alloy material, reduce grain boundary defects, and improve the processability and stability of the alloy material. Montmorillonite can also enhance the strength of the alloy material. The layered structure also extends the diffusion path of the penetrating molecules to a certain extent, improving the barrier properties of the alloy pipe, thereby obtaining an alloy pipe with stable structure and good anti-leakage properties. DETAILED DESCRIPTION

[0055] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.

[0056] Preparation Example 1

[0057] Preparation Example 1-1: A carboxylated polyethylene was prepared according to the following method:

[0058] 18 g of maleic anhydride and 2.5 g of dibenzoyl peroxide were added to acetone, stirred and dissolved to obtain a mixed solution with a mass fraction of 5%; the mixed solution was evenly mixed with 1 kg of polyethylene (PE100), and then melt-extruded (melt extrusion temperature was 175-190°C) to obtain carboxylated polyethylene.

[0059] Preparation Example 1-2, a carboxylated polyethylene, differs from Preparation Example 1-1 only in that the amount of maleic anhydride added is 18 g and the amount of dibenzoyl peroxide added is 2 g.

[0060] Preparation Example 1-3, a carboxylated polyethylene, differs from Preparation Example 1-1 only in that the amount of maleic anhydride added is 20 g and the amount of dibenzoyl peroxide added is 3 g.

[0061] Preparation Example 2

[0062] Preparation Example 2-1, an epoxidized polyamidoamine dendrimer was prepared according to the following method:

[0063] 10 g of polyamidoamine dendrimer (model G5-NH2) was added to 40 mL of ethanol solution, stirred and mixed, and then 280 g of epichlorohydrin was added. The temperature was raised to 60°C and stirred for 6 hours. Then, 10 mL of 50% potassium hydroxide solution was added and the solution temperature was adjusted to 35°C. The stirring reaction was continued for 2 hours. Finally, the epoxidized polyamidoamine dendrimer was obtained by filtration, extraction, vacuum distillation and drying.

[0064] Preparation Example 2-2, an epoxidized polyamidoamine dendrimer, differs from Preparation Example 2-1 only in that the amount of epichlorohydrin added is 260 g.

[0065] Preparation Example 2-3, an epoxidized polyamidoamine dendrimer, differs from Preparation Example 2-1 only in that the amount of epichlorohydrin added is 300 g.

[0066] Preparation Example 3

[0067] Preparation Example 3-1: A montmorillonite, which has been subjected to an organic treatment, comprises the following process steps:

[0068] Take 10g of montmorillonite (average particle size of 200 mesh) and disperse it in 100mL of water. Stir and disperse it at 60℃ for 2h, then add 7.5g of octadecyltrimethylammonium chloride, raise the temperature to 80℃, continue stirring and reacting for 2h, and finally obtain the organic-treated montmorillonite by vacuum filtration, washing, drying, grinding and sieving.

[0069] Example

[0070] Example 1: A built-in anti-leakage alloy pipe is prepared according to the following method:

[0071] S1. Weigh 1.5 kg of PET (intrinsic viscosity of 0.65 dL / g), 8.5 kg of the carboxylated polyethylene prepared in Preparation Example 1-1, 0.8 kg of the epoxidized polyamide amine dendrimer prepared in Preparation Example 2-1, 0.3 kg of the antioxidant DLTP, and 0.5 kg of montmorillonite (average particle size of 200 mesh), mix well, and extrusion granulate at 210 to 230 ° C to obtain a built-in layer masterbatch;

[0072] S2. The inner layer masterbatch and heat-resistant polyethylene (melt index of 0.6g / 10min under 190℃ / 2.16kg conditions) are extruded through a two-layer co-extruder, wherein the inner layer masterbatch is extruded to form an inner layer, and the thickness wall of the inner layer and the outer layer is 3:1, thereby obtaining an inner leak-proof alloy pipe.

[0073] Example 2 and Example 3 are a type of built-in anti-leakage alloy pipe. The only difference from Example 1 is that the ratio of the raw materials of the built-in layer is adjusted, as shown in Table 1:

[0074] Table 1 Formula table of Example 1 to Example 3

[0075] Example 1 Example 2 Example 3 PET / kg 1.5 1 2 Carboxylated polyethylene / kg 8.5 9 8 Epoxidized polyamidoamine dendrimer / kg 0.8 0.5 1 Antioxidant DLTP / kg 0.3 0.5 0.2 Montmorillonite / kg 0.5 0.3 0.6

[0076] Example 4, a built-in anti-leakage alloy pipe, is different from Example 1 only in that the carboxylated polyethylene prepared in Preparation Example 1-1 is replaced by an equal amount of the carboxylated polyethylene prepared in Preparation Example 1-2.

[0077] Example 5, a built-in anti-leakage alloy pipe, is different from Example 1 only in that the carboxylated polyethylene prepared in Preparation Example 1-1 is replaced by an equal amount of carboxylated polyethylene prepared in Preparation Example 1-3.

[0078] Example 6, a built-in anti-leakage alloy pipe, is different from Example 1 only in that the epoxidized polyamide amine dendrimer prepared in Preparation Example 2-1 is replaced by an equal amount of the epoxidized polyamide amine dendrimer prepared in Preparation Example 2-2.

[0079] Example 7, a built-in anti-leakage alloy pipe, is different from Example 1 only in that the epoxidized polyamide amine dendrimer prepared in Preparation Example 2-1 is replaced by an equal amount of the epoxidized polyamide amine dendrimer prepared in Preparation Example 2-3.

[0080] Example 8, a built-in anti-leakage alloy pipe, is different from Example 1 only in that the montmorillonite is replaced by an equal amount of the organically treated montmorillonite prepared in Preparation Example 3-1.

[0081] Comparative Example

[0082] Comparative Example 1 is an alloy pipe with built-in anti-leakage, which is different from Example 1 only in that the amount of the epoxidized polyamide amine dendrimer prepared in Preparation Example 2-1 added is 0.2 kg.

[0083] Comparative Example 2, a built-in anti-leakage alloy pipe, is different from Example 1 only in that the amount of epoxidized polyamidoamine dendrimer prepared in Preparation Example 2-1 added is 1.2 kg.

[0084] Comparative Example 3, a built-in anti-leakage alloy pipe, is different from Example 1 only in that an equal amount of polyamidoamine dendrimers is used to replace the epoxidized polyamidoamine dendrimers prepared in Preparation Example 2-1.

[0085] Comparative Example 4 is a built-in anti-leakage alloy pipe, which differs from Example 1 only in that an equal amount of SEBS grafted maleic anhydride compatibilizer is used to replace the epoxidized polyamide amine dendrimer prepared in Preparation Example 2-1.

[0086] Comparative Example 5 is an alloy pipe with built-in anti-leakage, which is different from Example 1 only in that the amount of montmorillonite added is 0.1 kg.

[0087] Comparative Example 6 is an alloy pipe with built-in anti-leakage, which is different from Example 1 only in that the amount of montmorillonite added is 0.8 kg.

[0088] Comparative Example 7 is an alloy pipe with built-in anti-leakage, which differs from Example 1 only in that montmorillonite is not added.

[0089] Comparative Example 8 is an alloy pipe with built-in leakage prevention. The only difference from Example 1 is that the carboxylated polyethylene prepared in Preparation Example 1-1 is replaced by an equal amount of unmodified polyethylene (PE100).

[0090] Performance testing

[0091] 1. Leakage Resistance Test: According to the relevant provisions of GB / T 18992.2-2003 "Cross-linked Polyethylene (PE-X) Piping Systems for Hot and Cold Water - Part 2: Pipes", the hydrostatic strength resistance of the alloy pipes obtained in the Examples and Comparative Examples was tested. The leakage or rupture of the alloy pipes under different pressures and time was observed. The test results are shown in Table 2.

[0092] 2. Mechanical Properties Test: According to the relevant description in GB / T 8804.3-2003 "Determination of tensile properties of thermoplastic pipes Part 3: Polyolefin pipes", the tensile strength of the alloy pipes obtained in the examples and comparative examples was tested. The test results are shown in Table 3.

[0093] Table 2 Anti-leakage performance test results

[0094]

[0095] Table 3 Mechanical properties test results

[0096]

[0097] According to Table 2 and Table 3, in combination with Example 1 and Example 8, it can be seen that the mechanical strength of Example 8 is slightly improved compared with Example 1. The reason is that the montmorillonite in Example 8 is subjected to organic modification treatment, which can improve the dispersibility in the alloy material and participate in the construction of the dynamic cross-linking network, which can further improve the mechanical properties of the alloy pipe.

[0098] Combining Example 1 and Comparative Examples 1 to 4, it can be seen that the hydrostatic pressure resistance and tensile strength of Comparative Examples 1 to 4 have decreased to varying degrees compared to Example 1, indicating that the anti-leakage ability and strength of Comparative Examples 1 to 4 have decreased. The reason is that the amount of cross-linking modifier added in Comparative Example 1 is reduced, and the density of the corresponding cross-linked network decreases, the compactness decreases, and thus the performance decreases. The amount of cross-linking modifier added in Comparative Example 2 is increased, which leads to excessive cross-linking. When resisting external loads, the load-bearing capacity decreases, and the anti-leakage performance decreases accordingly. The cross-linking modifier polyamide amine dendrimer in Comparative Example 3 has not been epoxidized and cannot form ester dynamic exchange bonds with the alloy material. The effect of improving the compactness, stability and self-repair ability of the alloy material decreases, and the performance decreases accordingly. In Comparative Example 4, a conventional compatibilizer is used to replace the cross-linking modifier, and a dynamic cross-linked network structure cannot be obtained. The barrier effect is limited and the anti-leakage ability decreases.

[0099] Combining Example 1 and Comparative Examples 5 to 7, it can be seen that the hydrostatic pressure resistance and tensile strength of Comparative Examples 5 to 7 all decreased to varying degrees compared to Example 1, indicating that the anti-leakage capabilities and strength of Comparative Examples 5 to 7 were reduced. This is because the reduced amount of montmorillonite added in Comparative Example 5 reduced the optimization of the alloy material's crystallization behavior and the improvement of its barrier and mechanical properties. Comparative Example 7, in which montmorillonite was not added, exhibited a more significant performance degradation. In Comparative Example 6, the amount of montmorillonite added was increased, but excessive montmorillonite easily agglomerated during mixing, resulting in stress concentration points in the resulting inner layer and a reduction in hydrostatic pressure load resistance.

[0100] Combining Example 1 and Comparative Example 8, it can be seen that the hydrostatic pressure resistance and tensile strength of Comparative Example 8 are both lower than those of Example 1. The reason is that the polyethylene in Comparative Example 8 has not undergone carboxylation modification, which makes it difficult to form a dynamic cross-linked network structure in the alloy material. The highly hydrophobic polyethylene molecular weight has poor compatibility with PET, the interfacial bonding force is weak, and there are a large number of interface defects, resulting in a decrease in the anti-leakage performance and mechanical properties of the obtained alloy pipe.

[0101] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus.

[0102] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A built-in anti-leakage alloy pipe, characterized in that: The alloy tube comprises an inner layer and an outer layer; the inner layer comprises the following raw materials in parts by mass: PET 10-20 parts; 80-90 parts of carboxylated polyethylene; 5-10 parts of cross-linking modifier; 2-5 parts of antioxidant; 3-6 parts of montmorillonite; The cross-linking modifier is an epoxidized polyamidoamine dendrimer.

2. The built-in anti-leakage alloy pipe according to claim 1, characterized in that: The raw materials of the carboxylated polyethylene include polyethylene, maleic anhydride and initiator in a mass ratio of 100:(1.5-2):(0.2-0.3).

3. The built-in anti-leakage alloy pipe according to claim 2, characterized in that: The initiator includes one or a combination of dicumyl peroxide and dibenzoyl peroxide.

4. The built-in anti-leakage alloy pipe according to claim 2, characterized in that: The carboxylated polyethylene is prepared according to the following method: Maleic anhydride and an initiator are added to a solvent, stirred and dissolved to obtain a mixed solution with a mass fraction of 5 to 10%; the mixed solution is evenly mixed with polyethylene, and then melt-extruded to obtain carboxylated polyethylene.

5. The built-in anti-leakage alloy pipe according to claim 1, characterized in that: The raw materials of the epoxidized polyamidoamine dendrimer include polyamidoamine dendrimer and epichlorohydrin in a mass ratio of 1:(26-30).

6. The built-in anti-leakage alloy pipe according to claim 5, characterized in that: The epoxidized polyamidoamine dendrimer is prepared according to the following method: Add polyamidoamine dendrimers to an alcohol solution, stir and mix, then add epichlorohydrin, raise the temperature to 50-60°C, stir and react for 5-6 hours, then add an alkaline catalyst, adjust the solution temperature to 30-35°C, continue stirring and react for 2-3 hours, and finally filter, extract, vacuum distill and dry to obtain epoxidized polyamidoamine dendrimers.

7. The built-in anti-leakage alloy pipe according to claim 1, characterized in that: The montmorillonite is subjected to an organic treatment; the organic treatment comprises the following steps: The montmorillonite is dispersed in water, stirred and dispersed at 60-65°C for 2-3 hours, then a cationic surfactant is added, the temperature is raised to 75-80°C, and the stirring reaction is continued for 2-3 hours. Finally, the organically treated montmorillonite is obtained by vacuum filtration, washing, drying, grinding and sieving.

8. The built-in anti-leakage alloy pipe according to claim 7, characterized in that: The mass ratio of the montmorillonite to the cationic surfactant is 1:(0.7-0.8); the cationic surfactant includes a combination of one or more of cetyltrimethylammonium bromide, octadecyltrimethylammonium chloride and octadecyldimethylbenzylammonium chloride.

9. The built-in anti-leakage alloy pipe according to claim 1, characterized in that: The material of the outer layer includes heat-resistant polyethylene.

10. A method for producing a built-in anti-leakage alloy pipe according to any one of claims 1 to 9, characterized in that: The process steps include: S1. Weigh the corresponding parts by mass of the built-in layer raw materials, mix them evenly and then extrude and granulate them to obtain a built-in layer masterbatch; S2. The inner layer masterbatch and the heat-resistant polyethylene are extruded through a two-layer co-extruder, wherein the inner layer masterbatch is extruded to form an inner layer, thereby obtaining an inner leakage-proof alloy pipe.